The Current Trend of Radiation Therapy for Patients with Localized Prostate Cancer - Kazuyuki Numakura; Mizuki Kobayashi; Yumina Muto; Hiromi Sato; Yuya Sekine; Ryuta Sobu; Yu Aoyama; Yoshiko Takahashi; Syuhei Okada; Hajime Sasagawa; Shintaro Narita; Satoshi Kumagai; et al. (Current Oncology, 2023)
A recent approach to radiotherapy for prostate cancer is the administration of high doses of radiation to the prostate while minimizing the risk of side effects. Thus, image-guided radiotherapy utilizes advanced imaging techniques and is a feasible strategy for increasing the radiation dose. New radioactive particles are another approach to achieving high doses and safe procedures. Prostate brachytherapy is currently considered as a combination therapy. Spacers are useful to protect adjacent organs, specifically the rectum, from excessive radiation exposure.